Intercultural Engagement Through Short-Term Faculty-Led Study Abroad: A Practitioner’s Guide with Multidisciplinary Perspectives from a Public University (Lightning Series, 2023)
The main objective of this edited volume is to offer pedagogically sound and creative ways of integrating elements of intercultural competence into class activities, tasks, and assignments in short-term faculty-led study abroad programs. The intercultural competencies, categorized in the areas of knowledge, skills, and attitudes, included characteristics such as awareness about self and other cultures, creative thinking, problem-solving, empathy, tolerance towards ambiguity, withholding judgment, to name a few. By purposefully embedding these characteristics in their course activities, faculty leaders could better assist their students in deepening intercultural and global competencies. These competencies prepared the students for a changing global work environment and helped them manage a more diverse workforce at home. This book is arranged into three sections. Section I provides the basic framework to understand short-term faculty-led study abroad programs both from a theoretical as well as administrative perspectives. Section II showcases 11 contributions from faculty leaders who share details regarding their programs demonstrating how intercultural competencies were strategically incorporated into the activities, tasks, and assignments of their study abroad curricula. Section III presents the conclusions with recommendations for faculty and administrators to plan and design short-term faculty-led study abroad programs. This book will contribute uniquely to the field by providing theoretically driven model courses from a broad spectrum of disciplines that would encourage the creation of new short-term faculty-led study abroad programs at the university level and empower current faculty leaders to strengthen or adapt their programs. The book will interest a broad readership of multidisciplinary study abroad educators, including faculty leaders, faculty leaders-in-training, faculty scholars, and administrators.